The Working Conditions in Canadian Hospitals. Constraints and Opportunity - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "The Working Conditions in Canadian Hospitals. Constraints and Opportunity," by Joan Kahn & William A. Westley.